Lactobacillus plantarum with Functional Properties: An Approach to Increase Safety and Shelf-Life of Fermented Foods - Behera, Sudhanshu S. (Biomed Res Int, 2018)
Lactobacillus plantarum (widespread member of the genus Lactobacillus) is one of the most studied species extensively used in food industry as probiotic microorganism and/or microbial starter. The exploitation of Lb. plantarum strains with their long history in food fermentation forms an emerging field and design of added-value foods. Lb. plantarum strains were also used to produce new functional (traditional/novel) foods and beverages with improved nutritional and technological features. Lb. plantarum strains were identified from many traditional foods and characterized for their systematics and molecular taxonomy, enzyme systems (α-amylase, esterase, lipase, α-glucosidase, β-glucosidase, enolase, phosphoketolase, lactase dehydrogenase, etc.), and bioactive compounds (bacteriocin, dipeptides, and other preservative compounds). This review emphasizes that the Lb. plantarum strains with their probiotic properties can have great effects against harmful microflora (foodborne pathogens) to increase safety and shelf-life of fermented foods.